Understanding the ‘identity of the righteous’ in the Sermon on the Mount - Cornelius, Elma M. (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
The Sermon on the Mount is a collection of Jesus’s teachings recorded in Matthew 5–7. It was addressed to the disciples and a large crowd of listeners on a mountainside near Capernaum. Francois Viljoen points to Matthew’s use of ‘righteousness’ in the Sermon on the Mount ‘as an instrument to define the identity of his community’. He illustrates that righteousness is a key concept in the Sermon on the Mount in 5:6, 10, 20 and 6:1, 33. He concludes that ‘the identity of the disciples is defined by their distinctive righteousness’ (Viljoen 2013:9). This article interpreted the ‘identity of the righteous’ in the Sermon on the Mount in the light of theories of social identity and status. Identity is understood as how individuals perceive themselves and are perceived by others – a complex concept encompassing various aspects of a person’s life. Status, closely related to identity, refers to one’s standing within society. This article addressed the following questions: Is the righteous a spiritual or religious identity? Is it a personal or group identity? Is being righteous a status? What is Jesus’s message about the righteous in the Sermon on the Mount? In interpreting the relevant passages in Matthew, the socio-historical background was considered. Lexical-syntactical, literary, and theological analyses were employed. To understand the nature of the righteous in these passages, various theories of social identity and status were applied. It was concluded that δικαιοσύνη in Matthew 5:29 and 6:1 refers to righteous behaviour. In the Beatitudes in Matthew 5:6 and 10, Jesus makes two pronouncements about righteousness as an achieved status. The δικαιοσύνη mentioned in Matthew 6:25–34 is a gift from God – an ascribed status under the grace of God. This status coheres with the spiritual and personal identity in Christ. Contribution: The primary contribution was to offer a scientific investigation and an understanding of the identity of the righteous in the Sermon on the Mount.